Influence and prediction mechanisms for discomfort and memory disturbance due to structure borne sound from a metro masked with fountain sound - Wang Qiaochu; Hongwei Wang; Cai Yangsheng; Zhang Yang; Yang Chenxi (Acta Acustica)
Previous studies suggested that introducing fountain sound could mitigate the discomfort and memory disturbance caused by structure borne sound from a metro, and proposed the prediction models for the discomfort after mitigation. However, these studies failed to identify the primary, secondary and significant influencing factors on the discomfort after mitigation, which hindered the proposal of optimal masking strategy and undermined the scientific validity of models. Additionally, previous analyses overlooked the primary, secondary and significant influencing factors on the memory disturbance after mitigation and lacked prediction model for it. Therefore, this study explored these aspects further. Based on auditory experiments, using partial least squares model and prediction model, this study found that considering total impact degree, the discomfort was predominantly influenced by the subjective loudness. However, the sound levels were the most important factors in determining the memory disturbance. The signal-to-noise ratio significantly influenced the discomfort but had no significant impact on the memory disturbance. Moreover, the subjective loudness emerged as the most effective predictor of the discomfort. While predicting the memory disturbance predominantly depended on the sound levels, and among the prediction models based on the sound levels, the predictive effectiveness of the energy summation model was comparable to that of the independent effects model. Furthermore, as global equivalent A-weighted sound level increased, the mitigation effect on discomfort became more evident, but its effectiveness in mitigating the memory disturbance gradually decreased. These conclusions could provide optimal strategies for enhancing such masking effects, and more effective prediction tools for such effects.